(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
The Early New English period (approximately 1500–1700) was marked by significant expansion and enrichment of the English vocabulary. During this era, English absorbed a large number of borrowings from Latin, Greek, French, Italian, Spanish, and Dutch, reflecting the influence of the Renaissance, trade, exploration, and cultural exchange. At the same time, native word-formation processes such as compounding, prefixation, suffixation, and conversion contributed to the creation of new terms.